Key Questions for Next-Generation Biomonitoring - Makiola, Andreas; Compson, Zacchaeus G.; Baird, Donald J.; Barnes, Matthew A.; Boerlijst, Sam P.; Bouchez, Agnès; Brennan, Georgina; Bush, Alex; Canard, Elsa; Cordier, Tristan; Creer, Simon; Curry, R. Allen; et al. (Frontiers in Environmental Science, 2020)
Classical biomonitoring techniques have focused primarily on measures linked to various biodiversity metrics and indicator species. Next-generation biomonitoring (NGB) describes a suite of tools and approaches that allow the examination of a broader spectrum of organisational levels - from genes to entire ecosystems. Here, we frame ten key questions that we envisage will drive the field of NGB over the next decade. While not exhaustive, this list covers most of the key challenges facing NGB, and provides the basis of the next steps for research and implementation in this field. These questions have been grouped into current- and outlook-related categories, corresponding to the organization of this paper.